Does congruence between a descendant entrepreneur’s personality traits and family business values matter for succession? - Ahmad, Zeshan; Chan, Wai Meng; Oon, Elaine Yen Nee (Frontiers in Psychology, 2023)
In this paper, we investigate two research queries pertaining to the success of small family business succession. First, we examine how the Big-5 personality traits of descendant entrepreneurs influence the success of their family business succession. Second, we investigate whether descendant entrepreneurs whose personality traits are congruent with the values of their family business, would lead to the success of their family business succession, through the mediating role of descendant entrepreneur-family business value congruence (DE-FBVC). Relying on the person-organization fit theory and utilizing a sample of 124 respondents, our results show that a descendant entrepreneur’s openness, extroversion, conscientiousness, and agreeableness traits are likely to lead to successful family business succession, but a descendant entrepreneur with neuroticism trait is unlikely to do so. In addition, our results reveal that the DE-FBVC mediates the relationship between openness and extroversion traits with succession success positively, but between neuroticism trait and succession success negatively. By contrast, we find that DE-FBVC does not mediate the relationship between conscientiousness and agreeableness traits with succession success. The findings of our study suggest that while four of the Big-5 personality traits matter for the success of small family business succession, specific personality traits of descendant entrepreneurs which are found to be congruent with the values of their family business, will also lead to succession success. Keywords: Big-5 personality traits, Family business value congruence, Succession success, Small family business, Person-organization fit theory